Botanical aspects, phytochemicals, and toxicity of Tamarindus indica leaf and a systematic review of antioxidant capacities of T. indica leaf extracts - Sookying, Sontaya; Duangjai, Acharaporn; Saokaew, Surasak; Phisalprapa, Pochamana (Frontiers in Nutrition, 2022)
Oxidative stress is a condition occurs when there is the imbalance between prooxidants and free radicals. It involves in cellular metabolism, aging, and immune response. Recently oxidative stress has been proved about its beneficial roles in human body. However, long term oxidative stress and high concentration of free radicals can lead to negative effects on organs, systems, and physiological conditions. Prooxidant or antioxidant, therefore, is one of the most important choices for the prevention of these anomaly. Tamarindus indica is a medicinal plant that has been reported as a source of antioxidants. The plants' leaves possess antioxidant effects according to many studies. However, these results have not yet been systematically summarized. The present systematic review summarizes and discusses about the in vitro antioxidant capacities of T. indica leaves. The plants' description and morphology, elements and phytochemical constituents, total phenolic and flavonoids contents and toxicity are also summarized and discussed here.